Geotechnical Properties of the Fagfog Quartzite for Curved-Cuts along Mugling Narayanghat Road Section - Paudyal, Sarmila; Panthee, Suman (Bulletin of the Department of Geology, 2018)
Slope cutting in hard and steep slopes are very difficult task. In Mugling-Narayanghat road section, near Mugling, hard quartzite rock was obstructing road expansion because of vertical slope. In the area rock of the Fagfog Quartzite is present which has very good geotechnical properties. In the area, rock mass classifications was carried out using RMR, Q and GSI where maximum and minimum rock mass class values are II and I respectively. Other properties of the area like unit weight (γ), uniaxial compressive strength (σci), Young’s modulus (Ei), Poisson’s ratio (ν) and RQD were also calculated according to the rock mass classification. The slope was designed in such a way that the maximum stability for minimum excavation. All the analysis were carried out in numerical modeling using FEM, as much as possible replicating real ground condition. From the analysis total displacement at suitable cut angles was determined. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 65-70